1. 1) X - Y = 3 >>> X = 3 + Y
2X + 3Y = 16 >>> 2(3+Y) + 3Y = 16 >>> 5Y = 16 - 6 = 10; Y = 2, X = 5
2) (4X + 3Y) + (3X - 2Y) = 11
7X + Y = 11
Y = 11 - 7X >>> 3X - 2(11-7X) = 12
17X = 34 >>> X = 2; Y = -3
2. Скорость первого = Х км/ч, а второго - Y км/ч
4X - 3Y = 12 (разница скоростей)
2X + 2Y = 20 (встреча пешеходов) >>> X + Y = 10 >>> Y = 10 - X
4X - 3(10 - X) = 12
4X - 30 - 3X = 12
7X = 42
X = 6 км/ч - скорость первого
Y = 4 км/ч - скорость второго
1. 1) X - Y = 3 >>> X = 3 + Y
2X + 3Y = 16 >>> 2(3+Y) + 3Y = 16 >>> 5Y = 16 - 6 = 10; Y = 2, X = 5
2) (4X + 3Y) + (3X - 2Y) = 11
7X + Y = 11
Y = 11 - 7X >>> 3X - 2(11-7X) = 12
17X = 34 >>> X = 2; Y = -3
2. Скорость первого = Х км/ч, а второго - Y км/ч
4X - 3Y = 12 (разница скоростей)
2X + 2Y = 20 (встреча пешеходов) >>> X + Y = 10 >>> Y = 10 - X
4X - 3(10 - X) = 12
4X - 30 - 3X = 12
7X = 42
X = 6 км/ч - скорость первого
Y = 4 км/ч - скорость второго